Cluster-assembled zirconia substrates promote long-term differentiation and functioning of human islets of Langerhans - Galli, A.; Maffioli, E.; Sogne, E.; Moretti, S.; Di Cairano, E.; Negri, A.; Nonnis, S.; Norata, Giuseppe; Bonacina, F.; Borghi, F.; Podestà, A.; Bertuzzi, F.; et al. (Nature Publishing Group, 2018)
Ex vivo expansion and differentiation of human pancreatic ß-cell are enabling steps of paramount importance for accelerating the development of therapies for diabetes. The success of regenerative strategies depends on their ability to reproduce the chemical and biophysical properties of the microenvironment in which ß-cells develop, proliferate and function. In this paper we focus on the biophysical properties of the extracellular environment and exploit the cluster-assembled zirconia substrates with tailored roughness to mimic the nanotopography of the extracellular matrix. We demonstrate that ß-cells can perceive nanoscale features of the substrate and can convert these stimuli into mechanotransductive processes which promote long-term in vitro human islet culture, thus preserving ß-cell differentiation and function. Proteomic and quantitative immunofluorescence analyses demonstrate that the process is driven by nanoscale topography, via remodelling of the actin cytoskeleton and nuclear architecture. These modifications activate a transcriptional program which stimulates an adaptive metabolic glucose response. Engineered cluster-assembled substrates coupled with proteomic approaches may provide a useful strategy for identifying novel molecular targets for treating diabetes mellitus and for enhancing tissue engineering in order to improve the efficacy of islet cell transplantation therapies.